An experiment on corruption and gender - Fernanda Rivas
There exists evidence in the social science literature that women may be more relationshiporiented, may have higher standards of ethical behavior and may be more concerned with the common good than men are. This would imply that women are more willing to sacrifice private profit for the public good, and this would be especially important for political life. Many papers with field data have found deference’s in the corrupt activities of males and females, but given their different insertion in the labor market and in politics, it is not clear if the differences are due to differences in opportunities or real gender differences. The aim of this paper is to see if women and men, facing the same situation behave in a different way, as suggested in the field-data studies, or on the contrary, when women are in the same position as men they behave in the same way. The results found in the experiment show that women are indeed less corrupt than men. This suggests that increasing women’s participation in the labor force and politics would help to reduce corruption.corruption, gender, experiment